Progettando città Riflessioni sul metodo della Progettazione Urbana - Capestro, Antonio (Strumenti per la didattica e la ricerca, 2012)
City and territory are currently experiencing a phase of development, or crisis, depending on whether they manage to form the know-how to respond to the current exponential evolution. Know-how that has to make a critical assessment of the fabric of structures, cultures and inherited layouts. Between continuity and innovation, contemporary town planning culture creates the basis for a more flexible model that can seek out new continuities by interpreting the present discontinuity, dissent, difference, decentralization and dispersion. This implies a processual space and new aesthetics of sense and therefore presupposes new themes able to redefine the physical-relational relationships by combining cultural roots, functional requirements and spatial layouts.